Analysis of IMRT patient specific quality assurance using EPID measurement data from the Halcyon linear accelerator - Shinhaeng Cho; Jea-Uk Jeong; Yong Hyub Kim; Mee Sun Yoon; Taek-Keun Nam; Sung-Ja Ahn; Ju-Young Song (PLoS ONE, 2026)
This study investigated the characteristics of electronic portal imaging device (EPID)-based perpendicular field-by-field patient-specific quality assurance (PFF-PSQA) on the Halcyon linear accelerator by comparing them with the true composite (TC)-PSQA performed using the Delta 4 Phantom+ (ScandiDos, Sweden) system. Both methods demonstrated excellent dose agreement under the AAPM TG-218 gamma criteria and strong correlations were observed between their results across prostate, nasopharynx, and breast cases. However, gamma passing rate (GPR) reductions due to treatment isocenter displacements were more pronounced in TC-PSQA, whereas EPID-based PFF-PSQA consistently showed relatively higher and more stable GPR values. A two-way repeated measures ANOVA analysis confirmed a significant difference in sensitivity to displacement-induced errors, supporting the clinical robustness of EPID-based PFF-PSQA. In addition, EPID-based PFF-PSQA yielded tolerance and action limits of 99.5% and 99.4%, respectively, which exceed the conventional 95% and 90% thresholds specified in the report of American association of physicists in medicine (AAPM) TG-218, highlighting the necessity of refining evaluation criteria for this approach. Overall, these findings indicate that EPID-based PFF-PSQA can serve as a reliable and clinically alternative to TC-PSQA.